Vertically Stacked vdW Double Heterojunction Photodiode with Ultrawide Bandgap Gallium Oxide Electron Reservoir - Lee, Chan Ho; Park, Youngseo; Kim, Sungkyu; Jeong, Yeong Je; Ahn, Yeong Hwan; Kim, Young Chul; Heo, Junseok; Yoo, Geonwook (Advanced Optical Materials, 2022)
Co-integration of visible and infrared (IR) photodetection into a simple configuration is of essential importance for broadband multispectral imaging, and various heterostructures based on group IV, III–V, and recent 2D semiconductors have been studied in efforts to circumvent limits on photoresponsivity and response speed in IR ranges. In this work, a vertically stacked double heterojunction (DHJ) photodiode (PD) with ultrawide-bandgap gallium oxide (Ga2O3) is reported on, and the performance is compared with p-WSe2/n-Ge PD. The fabricated n-Ga2O3/p-WSe2/n-Ge PD responds to a broad spectral range from vis to shortwave IR (SWIR) (1550 nm) with a response time of ≈2.6 µs and responsivity of 17.2 A W−1. The superior performance is attributed to amplified photocurrent gains, and the additional n-Ga2O3 has a high electron carrier density with negligible hole density at room temperature and thus, can play a role as an electron reservoir while being transparent to the spectral ranges. vScanning photocurrent microscopy analysis is performed to provide the mechanism. The demonstrated SWIR imaging shows that the proposed DHJ provides a potential pathway for high-speed multispectral vision applications.
Keywords: Cointegration; Double heterojunctions; Electron reservoir; Heterojunction photodiodes; Performance; Photo detection; Spectral range; Ultra-wide; Vertical stacking; WSe 2/ge; gallium oxide; heterojunctions; photodiodes; vertical stacking; WSe 2/Ge